SPE Annual Technical Conference and Exhibition 1989
DOI: 10.2118/19692-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Oil Destabilization of Nitrogen Foams in Porous Media

Abstract: When applied as conformance treatments, foams are required to effectively reduce gas injectivities over prolonged periods of time. Frequently, this ability must be manifested in the presence of a residual oil saturation which often exerts a destabilizing effect on foam and the capacity to generate foam. In this study, the capacity to generate and sustain foam in the presence of a residual oil saturation was examined by each of two methods. The first method monitored the in-situ generation of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Oil recovery by foam has been attributed to the emulsification and imbibition of oil into foam lamellae (14,45) . A very slow approach to steady state and continued slow oil production have previously been observed with nitrogen-and CO 2 -foams that exhibit some sensitivity to oil (16,17,46,47) . When the methane fractional flow was lowered to 72%, the pressure drop increased more steeply, correlating directly with an increased rate of oil production [ Figure 6(b)].…”
Section: Transient Pressure Behaviour and Oil Recovery During Foam Flmentioning
confidence: 83%
“…Oil recovery by foam has been attributed to the emulsification and imbibition of oil into foam lamellae (14,45) . A very slow approach to steady state and continued slow oil production have previously been observed with nitrogen-and CO 2 -foams that exhibit some sensitivity to oil (16,17,46,47) . When the methane fractional flow was lowered to 72%, the pressure drop increased more steeply, correlating directly with an increased rate of oil production [ Figure 6(b)].…”
Section: Transient Pressure Behaviour and Oil Recovery During Foam Flmentioning
confidence: 83%
“…The overwhehning majority of d,_tt_ available in the literature confirms that much less gas mobility reduction is obtained in the presence of oil tll,m in it;s td)sence [5,6,18,25,44,60,78,86], In corefloods, foam propagation is reL,_rded in the presence ,,f oil, Being l;he non-wel;ting phase in sands, oil occupies the l_rge pores t_hus blocking a few of tile foa, rn generatiion sities ld/li, Therefore, fo_ma does not propaga, t,e until some of the ,,ii is disl)l_uzed, The desl;_billz,ation of fomn by oil in a porous medium is due to oil penetr_tion of the gas/liquid interfa,ce followed by lamellae rupture [106]. Result, s of Lau _md O'I3rien [76] show tl_at; flu' presence of a spre_cling oil slows down foam generation and decreases foam propagation rat;e, Mmllowe and l:{,a,dl<e [81] indicated that foam sta,bility in porous media is'dependent ttpoll l,he stability of pseudoemulsiozl films (liquid films between oil and g_s).…”
Section: Presence Of Oilmentioning
confidence: 99%
“…• The presence of oil has a destabilizing effect on foam with mos foaming surfactants q [5,6,18,25,44,60,67,78,81,86,106]. …”
mentioning
confidence: 99%
“…The presence of oil is of primary importance since its effect on lamellae stability depends on the extent to which the foam lamellae interact with the oil . Since foam generation and propagation in porous media is strongly oil‐specific, oil‐insensitive foams have been shown to propagate faster than oil‐sensitive foams . Earlier studies showed that alkenes with a shorter carbon chain tended to be more detrimental to foam stability, which was determined by performing a series of bulk experiments .…”
Section: Introductionmentioning
confidence: 99%
“…[16] Since foam generation and propagation in porous media is strongly MONTH 2019 THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING 1 oil-specific, oil-insensitive foams have been shown to propagate faster than oil-sensitive foams. [17][18][19] Earlier studies showed that alkenes with a shorter carbon chain tended to be more detrimental to foam stability, which was determined by performing a series of bulk experiments. [8] One group of researchers stated that there is a specific critical oil saturation above which foam does not form, while others argued that high-quality foam can still be generated at relatively high residual oil saturation.…”
Section: Introductionmentioning
confidence: 99%